Peran Keberagaman Gender dalam Memoderasi Pengaruh Pengungkapan Manajemen Risiko terhadap Kinerja Perusahaan - Dewi Nurul Arofah; Suwarno Suwarno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study measures how risk management disclosure impacts firm performance, using gender diversity as a moderating variable, as firm performance is a key indicator for achieving business goals. Given the complex risks in today's business environment, companies must implement and disclose risk management practices transparently to improve governance effectiveness and investor confidence. The population of this study covers manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2024, with a sample of 52 companies selected through purposive sampling. This research employs a quantitative approach using secondary data from annual reports, which were analyzed using SmartPLS version 4 software via Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that risk management disclosure has a positive and significant effect on firm performance, and gender diversity as a moderating variable further strengthens the relationship between risk management disclosure and performance. Overall, these results suggest that transparent risk management supported by gender diversity on the board of directors can enhance monitoring effectiveness, improve the quality of strategic decision-making, and boost sustainable firm performance.